Pengaruh Insentif terhadap Kinerja Karyawan Pada PT. Bintang Jaya Auto Kota Jambi - Mecintuti Saridewi (Science of Management and Students Research Journal (SMS), 2022)
The purpose of this study was to determine incentive and employee performance and to identify and analyze the effect of incentive on employee performance at PT Bintang Jaya Auto, Kota Jambi. In this research, the research method used is a qualitative and quantitative descriptive method. This form of research is a type of quantitative research, this method has been used for a long time in other that it has become a tradition of research methods. The types of data sources used are primary data and secondary data. The data collection methods are Library Research, Field Research and Questionnaires. The population and sample this study used the census method and totaled 37 people. PT. Bintang Jaya Auto is a company engaged in the automotive sector that has been selling used cars since 2017 by Hendra Purnama Jaya as the Owner or Main Director of PT. Bintang Jaya Auto. By selling various brands of car, namely Toyota, Honda, Nissan, Daihatsu, Suzuki, and so on. This company has several branches, namely Garasi Bintang Showroom, Kharisma Jaya Mobilindo Showroom, Gajahmada Auto Showroom and BN Mobilindo Showroom. From the results of research on incentive and employee performance at PT Bintang Jaya Auto Kota Jambi, it showed a high category. Wherever the Incentive variable the average score is 148 in the high category. The dimension of the highest variable is the dimension of giving awards and promos, in the high category is 153. On the other hand, employee performance variables average score of 150.5 in the high category. In other way, the highest employee performance variable dimension is the quality dimension, which is 152.3 in the high category. Meanwhile, from the t test it is concluded that incentives have a significant effect on employee performance at PT Bintang Jaya Auto Kota Jambi, where tcount for incentive is greater than ttabel (4.886> 1.6895). And incentive have a positive and significant influence on employee performance. This is indicated by tcount> ttabel, and pro.sig (0.000) <α (0.05).